Effectiveness of Dietary Habits on Urolithiatic Patients at Urinary Units in Baghdad Teaching Hospitals - salih, Maqdad; Kadhim, Haleema (Iraqi National Journal of Nursing Specialties, 2013)
Objectives: The study aims at finding the effectiveness of dietary habits on urolithiatic patients at Urinary Unitsin Baghdad Teaching Hospitals.Methodology: A quantitative descriptive study was conducted to identify the effectiveness of dietary habits on(100) of urolithiatic patients in Urinary Units at Baghdad Teaching Hospitals starting from May 2011 to Sep.2012.Data were collected through the use of constructed check list of the questionnaire format, whichconsists of two parts: - The first part: is related to the patient's demographic variables ; the second part: isconstructed to serve the purpose of the study (effectiveness of the dietary habits). The total number of itemsof the questionnaire is (69) items. Validity of the questionnaire format was determined through a panel of (23)experts and the reliability is determined through a pilot study. Descriptive statistical analysis procedures (thefrequency, and the percentage) is used for the data analysis of this study.Results: The data of this study shows that the urinary tract system (UTS) stone formation (SF) is: {Activated(increased) by fried foods, soft drinks (Pepsi cola and Coca cola), tea, red meat, eggs, ice cream, tomato,potato, pepper, urinary tract infection (UTI), obesity, hot areas, low education; and, Inhibited (decreased) bywater, coffee, cacao, natural raisin and apricot ( fresh, syrup, dry), Artificial beverage (Seven up, Miranda),herbs, milk, cheese and butter, white meat (chicken, fish), vitamins}. So, it would be concluded that there is aclear effect of ''dietary habit'' on urinary stone formation.Recommendations: The study recommended that the patients should be given booklets or manual guidesincluding the following (Type of his/her urinary stone. Accordingly should be advised to: Reduction of his/herdietary habit by preventing certain materials and increasing others to avoid stone recurrence; Advised to drinkliquids especially water 3-4 l/day, Never delay urine voiding, and add the Milk to tea to decrease tea'spromotion to stone formation because the tea is high content of oxalate).